1991
DOI: 10.1007/bf00314785
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of the c-erbB oncogene is associated with malignancy in primary tumours of neuroepithelial tissue

Abstract: In various primary brain tumours of neuroepithelial tissue recombinant DNA techniques were used to demonstrate changes of the epidermal growth factor receptor gene, which is homologous to the c-erbB oncogene. Twenty-one of 40 grade III/IV tumours, but only 1 of 16 grade I/II tumours were found to contain amplified and/or rearranged c-erbB sequences. This highly significant difference suggest that c-erbB amplification, rearrangement, or both, are important steps in malignant transformation in a subset of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…When glioblastoma cells are cultured in vitro, they lose both their amplified EGFR genes and double-minute chromosomes [93]. Although amplification of the EGFR gene is associated with increasing histologic grade of tumors (e.g., glioblastoma versus anaplastic astrocytoma), within patients with glioblastomas the presence or absence of EGFR gene amplification was not correlated with a tumor's morphologic characteristics or with survival [78,94]. However, recent studies have reported a shorter median survival in patients with amplification, indicating that amplification may be a significant prognostic factor [95].…”
Section: Molecular and Cytogenetic Studiesmentioning
confidence: 99%
“…When glioblastoma cells are cultured in vitro, they lose both their amplified EGFR genes and double-minute chromosomes [93]. Although amplification of the EGFR gene is associated with increasing histologic grade of tumors (e.g., glioblastoma versus anaplastic astrocytoma), within patients with glioblastomas the presence or absence of EGFR gene amplification was not correlated with a tumor's morphologic characteristics or with survival [78,94]. However, recent studies have reported a shorter median survival in patients with amplification, indicating that amplification may be a significant prognostic factor [95].…”
Section: Molecular and Cytogenetic Studiesmentioning
confidence: 99%
“…Increased levels of EGFR expression have been demonstrated in the majority of oligodendrogliomas and are rarely due to EGFR gene amplification (137,(201)(202)(203)(204). Based on the approximately equal incidence of EGFR overexpression in both lowand high-grade oligodendrogliomas, this alteration is most likely an early event in oligodendroglial tumor development and not associated with malignant progression of these tumors (201).…”
Section: Egfrmentioning
confidence: 99%
“…[3] In oligodendrogliomas, increased mRNA and protein expression was observed in up to 80%. [134], [135], [147]- [153] Similar expression levels for EGFR were found in Grades II and III oligodendrogliomas, indicating that this alteration is an early event in tumorigenesis. However, in contrast to high-grade astrocytomas, most studies reported only EGFR amplification in a few samples of anaplastic oligodendrog-lioma.…”
Section: Oncogenesmentioning
confidence: 97%
“…Only in a few samples, amplification of EGFR and PDGFRA was seen in anaplastic oligodendrogliomas. [79], [115], [134]- [137] Promoter hypermethylation in oligodendrogliomas Epigenetic silencing may play an important role in the induction and progression of oligodendrogliomas. [86], [138] In fact, a high throughput approach identified large numbers of hypermethylated genes.…”
Section: Allelic Loss Of Chromosome 1p and 19qmentioning
confidence: 99%
See 1 more Smart Citation